Analytical investigation of MgO-CuO\H2O, hybrid nanofluid MHD stagnation point flow with the influence of viscous dissipation for enhancement of heat transfer ratio - Rehman, Ali; Alhefthi, Reem K.; İnç, Mustafa; Jan, Rashid (World Scientific Publ Co Pte Ltd, 2024)
In this research work, we will carry out analytical investigation of MgO-CuO\H2O, hybrid nanofluid magnetohydrodynamics (MHD) stagnation point flow with the influence of viscous dissipation for enhancement of heat transfer ratio. The flow system takes into account the impact viscous dissipation and transport dependence on the shape factor. Furthermore, velocity and temperature at the stretching surface are also considered in this study. To convert a collection of PDEs to nonlinear ODEs, we applied appropriate transformations. We utilize the Homotopy analysis method (HAM) to solve this set of equations. A physical description is used to simulate and evaluate the structures of flow features such as velocity, skin friction, Nusselt number and temperature profiles in response to changes in developing factors, the effects of different factors on temperature and velocities are shown in the form of graphs. It is hoped that this theoretical approach would contribute positively to improve the heat transformation ratio to satisfy the demands of the manufacturing and engineering sectors.
Keywords: Hybrid nanofluid; magnetohydrodynamics (MHD); HAM; stretching surface; viscous dissipation